Wanna Bet? Investigating the Factors Related to Adolescent and Young Adult Gambling - Amelia Rizzo; Valentina Lucia La Rosa; Elena Commodari; Dario Alparone; Pietro Crescenzo; Murat Yıldırım; Francesco Chirico (MDPI AG, 2023)
For many adolescents and young adults, gambling can represent an attractive and exciting form of entertainment, a way to take risks and explore new experiences. However, gambling also poses a significant risk for this age group. Research suggests that adolescents and young adults are particularly vulnerable to the negative consequences of gambling, including addiction, financial difficulties, and mental health issues. This paper aims to critically examine data on adolescent and young adult gambling, focusing on the risk factors associated with gambling behavior. A total of 326 subjects (Mage = 19.01; SD =2.72), of whom 65.5% were female, completed a protocol containing a demographic sheet, the Lie/Bet Questionnaire, the Seven Domains Addiction Scale (7DAS), a subscale of the Addictive Behavior Questionnaire and the Coping Inventory for Stressful Situations (CISS). Specifically, we explored the impact of sociodemographic, environmental, psychological, and cognitive factors on adolescent and young adult gambling behavior. Clinical implications and future directions are discussed.